Macrophage migration inhibitory factor contributes to immunopathogenesis during Plasmodium yoelii 17XL infection - Salazar-Castañón, Víctor H.; Juárez-Avelar, Imelda; Legorreta-Herrera, Martha; Rodriguez-Sosa, Miriam (Frontiers in Cellular and Infection Microbiology, 2022)
Macrophage migration inhibitory factor (MIF) is a cytokine recognized regulator of the inflammatory immune response associated with several immune cells that produce inflammatory cytokines such as IL-1β, IL-6, IL-12, IL-18, and TNF-α. This study aimed to understand the effect of MIF on the immune response and pathogenesis during Plasmodium infection. Wild-type (Wt) and MIF knockout (Mif-/-) mice were intravenously infected with 1×103Plasmodium yoelii (Py) 17XL-parasitized red blood cells. Our data showed that Py17XL-infected Wt mice died 11 days postinfection, while Mif-/- mice showed reduced parasitemia and an increase in their survival at day 11 up to 58%, importantly they succumb up to day 21 postinfection. The increased survival rate in Mif-/- mice was associated with less severe cachexia and anemia as a result of a mixed Th1/Th2 cytokine profile, high levels of IL-12, IL-17/IL-4, and IL-10 in serum; and high levels of IL-4 and IL-10, and low levels of IFN-γ in spleen cells compared to Py17XL infected Wt mice. Moreover, macrophages (Mφs) from Mif-/- mice exhibited higher concentrations of IL-10 and IL-12 and reduced levels of TNF-α and nitric oxide (NO) compared to Py17XL-infected Wt mice. These results demonstrate that MIF has an important role in regulating the immune response associated with host pathogenesis and lethality, which is relevant to consider in preventing/reducing complications in Plasmodium infections.